Peran Media Sosial Instagram dalam Mendukung Event Activation Kalbe Consumer Health Branch Bogor - R. Moh Baehaki; Alfi Rahmawati (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
This study discusses the effectiveness of using Instagram as a digital marketing tool to support event activation activities carried out by Kalbe Consumer Health Branch Bogor. The purpose of this research is to analyze how Instagram contributes to increasing audience engagement, strengthening brand image, and expanding the reach of promotional activities. The research method used is a qualitative descriptive approach through observation, documentation, and analysis of social media content related to Kalbe’s event activations. The results show that Instagram plays a significant role in enhancing public awareness, fostering interactive engagement, and supporting sales performance during event promotions. Moreover, the integration between online activities and offline events creates a consistent and impactful communication strategy. Overall, the use of Instagram has proven to be an effective medium for strengthening brand presence and optimizing marketing communication at Kalbe Consumer Health Branch Bogor